A Benzopyronin-Based Two-Photon Fluorescent Probe for Ratiometric Imaging of Lysosomal Bisulfite with Complete Spectral Separation - Tamima, Umme; Santra, Mithun; Song, Chang Wook; Reo, Ye Jin; Ahn, Kyo Han (Analytical chemistry (Washington), 2019)
Bisulfite (HSO3 –), which equilibrates with sulfite (SO3 2–) and sulfur dioxide (SO2) in aqueous media, can be produced endogenously during oxidation of hydrogen sulfide or sulfur-containing amino acids. Lysosomes, known as the scavengers of living cells, play a crucial role in the metabolic process, and bisulfite is often produced inside the lysosomes. Therefore, detection of bisulfite in lysosomes is a subject of significant interest. Herein, we disclose a lysosome-targeting, two-photon excitable, and ratiometric signaling (near-infrared/green) fluorescent probe that detects bisulfite through a fast 1,6-conjugate addition reaction. The probe shows excellent selectivity toward bisulfite over other biologically relevant species. Notably, the probe allows ratiometric fluorescence imaging of lysosomal bisulfite with complete spectral separation under one-photon as well as two-photon excitation conditions.